Research on interaction of controllable series compensation and traditional PSS to suppress low-frequency oscillation - Ming Li; Wenbo Ren; Anqing Chen; Jiayuan Gong; Jingnan Wang (Frontiers in Energy Research, 2023)
In order to make the power transmission more stable and ensure the safe operation of the system, a study on the interaction of controllable series compensation and traditional PSS to suppress low-frequency oscillation is proposed. Firstly, the lead-slip angle is adjusted by the lead-lag module of the PSS limit stabilizer to eliminate the reverse modulation phenomenon, and the series compensation is used to optimize the parallel transmission lines and lines of different voltage levels to improve the stability of the long-distance transmission system. Secondly, the phase compensation method is used to set the parameters of the TCSC and PSS damping controllers, the characteristics of the rotor system are judged by the damping ratio, the sensitivity characteristic root is extracted, and the maximum parameters affecting the mode are determined; finally, the genetic algorithm is introduced to coordinate the damping controller to increase the oscillation. Mode damping, constraining the range of each tuning parameter, enabling coordinated optimization. Experiments show that the method in this paper can effectively suppress low-frequency oscillation and ensure the safety and stability of the power system.